Group portrait of leather title holders - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows group portrait of gay and lesbian leather title holders outside Greg's Ballroom on the one year anniversary of the bar. Three men wear their sashes with their titles partially visible.